2020
DOI: 10.7150/ijbs.42965
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic use of Statins as non-lipid-lowering drugs

Abstract: Statins, known as HMG-CoA reductase (HMGCR) inhibitors, have primarily been utilized for metabolic and angiographic medical applications because of their cholesterol-lowering effects. Similar to other drugs, statins may also induce a series of potential side effects. Statins inhibit the HMGCR (rate-limiting enzyme) activity in early stages of mevalonate pathway and then indirectly affect a number of intermediate products, including non-sterol isoprenoids (coenzyme Q10, dolichol etc.), which can result in impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 74 publications
0
29
0
1
Order By: Relevance
“…The inhibitory function of statins on HMG-CoA reductase resulted in depletion of cholesterol and isoprenoids in MVA pathway 19 , 55 . Statins thus have therapeutic application in diseases like inflammatory disease, cancer, and neurodegenerative disease including AD, PD, and MS, probably due to its pleiotropic effects independent of lowering cholesterol levels 24 26 , 56 . However, impacts of statins on ALS have gained less attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory function of statins on HMG-CoA reductase resulted in depletion of cholesterol and isoprenoids in MVA pathway 19 , 55 . Statins thus have therapeutic application in diseases like inflammatory disease, cancer, and neurodegenerative disease including AD, PD, and MS, probably due to its pleiotropic effects independent of lowering cholesterol levels 24 26 , 56 . However, impacts of statins on ALS have gained less attention.…”
Section: Discussionmentioning
confidence: 99%
“…By lowing LDL levels, statins have been widely used in the clinic for treating hypercholesterolemia, cardiovascular, and cerebrovascular disease 21 23 . Moreover, the pleiotropic effects (independent cholesterol) of statins have a protective effect in many diseases, including AD, PD, and multiple sclerosis (MS) 24 26 . However, accumulating data have suggested that statins increased risk of diabetes, liver disorders, or myopathy 27 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of statins on cardiovascular morbidity and mortality in patients with and without atherosclerotic disease has been well proven. Furthermore, statins appear to exert pleiotropic effects independent of their lipid-lowering properties, including effects on diabetes, neurological diseases, coronary heart disease, inflammation and cancer [ 16 ]. Given the anticancer effects of statins, and the fact that statins are well-tolerated, inexpensive, and less toxic than conventional chemotherapy drugs, many researchers considered repurposing statins as a promising strategy for the treatment of cancer.…”
Section: Conventional and Off-label Of Statinsmentioning
confidence: 99%
“…They are not only used to reduce low-density lipoprotein (LDL) cholesterol and prevent cardiovascular diseases but also play a role in many other conditions, including inhibiting inflammatory reaction, antioxidants, improving endothelial function, and even inhibiting mitosis of cancer cells. [5][6][7][8] For example, statin was identified as a potential neuroprotective agent that targeted the inflammatory response following ICH. However, the use of statin was usually limited by its inherent drawbacks.…”
Section: Introductionmentioning
confidence: 99%